Variation of PPARG Expression in Chemotherapy-Sensitive Patients of Hypopharyngeal Squamous Cell Carcinoma - Meng Lian; Yong Tao; Jiaming Chen; Xixi Shen; Lizhen Hou; Shaolong Cao; Jugao Fang (PPAR Research)
Our previous study showed that the upregulation of peroxisome proliferator-activated receptor gamma (PPARG) could promote chemosensitivity of hypopharyngeal squamous cell carcinoma (HSCC) in chemotherapeutic treatments. Here, we acquired two more independent expression data of PPARG to validate the expression levels of PPARG in chemotherapy-sensitive patients (CSP) and its individualized variations compared to chemotherapy-non-sensitive patients (CNSP). Our results showed that overall PPARG expression was mildly downregulated (log fold change=−0.55; p value = 0.42; overexpression in three CSPs and reduced expression in four CSPs), which was not consistent with previous results (log fold change=0.50; p=0.22; overexpression in nine CSPs and reduced expression in three CSPs). Both studies indicated that PPARG expression variation was significantly associated with the Tumor-Node-Metastasis (TNM) stage (p=7.45e−7 and 6.50e−4, for the first and second studies, respectively), which was used as one of the predictors of chemosensitivity. The new dataset analysis revealed 51 genes with significant gene expression changes in CSPs (LFC>1 or <-1; p value < 0.01), and two of them (TMEM45A and RBP1) demonstrated strong coexpression with PPARG (Pearson correlation coefficient>0.6 or <-0.6). There were 21 significant genes in the data from the first study, with no significant association with PPARG and no overlap with the 51 genes revealed in this study. Our results support the connection between PPARG and chemosensitivity in HSCC tumor cells. However, significant PPARG variation exists in CSPs, which may be influenced by multiple factors, including the TNM stage.